Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.4025/actascianimsci.v40i0.37230
|View full text |Cite
|
Sign up to set email alerts
|

<b>Appraisal of purple coneflower (<i>Echinacea purpurea</i>) extract on production performance, internal organs, and gut microflora of japanese quail

Abstract: ABSTRACT. An experiment was carried out to evaluate the effects of Echinacea purpurea (EP) extract at 5 levels (0, 0.25, 0.5, 1 or 2 mL L -1 of drinking water) on performance, internal organs and gut microflora of Japanese quail (Coturnix coturnix Japonica). The results showed that EP extract decreased feed intake and body weight gain of quails. The feed conversion ratio of quails fed with EP extract at the level of 0.5 ml L -1 drinking water was significantly decreased compared to the control group. Adding EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Feed additives research on different poultry species has been dramatically intensified in recent decade (Hajati, Gilani, & S., 2019;Seifi, Khoshbakht, Hajati, & Gilani, 2018). Interestingly, it has been shown that antibiotic replacers such as prebiotic and probiotic are more fruitful under suboptimal conditions such as stress (Fowler, Kakani, Haq, Byrd, & Bailey, 2015;Seifi, Khoshbakht, Sayrafi, & Gilani, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Feed additives research on different poultry species has been dramatically intensified in recent decade (Hajati, Gilani, & S., 2019;Seifi, Khoshbakht, Hajati, & Gilani, 2018). Interestingly, it has been shown that antibiotic replacers such as prebiotic and probiotic are more fruitful under suboptimal conditions such as stress (Fowler, Kakani, Haq, Byrd, & Bailey, 2015;Seifi, Khoshbakht, Sayrafi, & Gilani, 2018).…”
Section: Introductionmentioning
confidence: 99%